2005
DOI: 10.1021/bm0501454
|View full text |Cite
|
Sign up to set email alerts
|

Polymersome Encapsulated Hemoglobin:  A Novel Type of Oxygen Carrier

Abstract: Bovine hemoglobin (Hb) was encapsulated inside polymer vesicles (polymersomes) to form polymersome encapsulated Hb (PEH) dispersions. PEH particles are 100% surface PEGylated with longer PEG chains and possess thicker hydrophobic membranes as compared to conventional liposomes. Polymersomes were self-assembled from poly(butadiene)-poly(ethylene glycol) (PBD-PEO) amphiphilic diblock copolymers with PBD-PEO molecular weights of 22-12.6, 5-2.3, 2.5-1.3, and 1.8-0.9 kDa. The first two diblock copolymers possessed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
168
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(171 citation statements)
references
References 61 publications
2
168
0
1
Order By: Relevance
“…Lee et al successfully encapsulated myoglobin, hemoglobin, and albumin in PEO-b-PBD based polymer vesicles at varying degrees of encapsulation efficiency [5]. Arifin and Palmer further demonstrated that bovine hemoglobin (Hb) could be encapsulated inside PEO-b-PBD polymer vesicles with oxygen affinities similar to those of human red blood cells; they demonstrated that these "polymersomes-encapuslated hemoglobin" (PEH) dispersions could store and transport Hb and potentially act as in vivo oxygen therapeutics [47]. The ability to encapsulate proteins within polymersomes provides a promise for future protein therapies, which are currently facing delivery obstacles.…”
Section: Therapeutic Applications Of Polymersomesmentioning
confidence: 99%
“…Lee et al successfully encapsulated myoglobin, hemoglobin, and albumin in PEO-b-PBD based polymer vesicles at varying degrees of encapsulation efficiency [5]. Arifin and Palmer further demonstrated that bovine hemoglobin (Hb) could be encapsulated inside PEO-b-PBD polymer vesicles with oxygen affinities similar to those of human red blood cells; they demonstrated that these "polymersomes-encapuslated hemoglobin" (PEH) dispersions could store and transport Hb and potentially act as in vivo oxygen therapeutics [47]. The ability to encapsulate proteins within polymersomes provides a promise for future protein therapies, which are currently facing delivery obstacles.…”
Section: Therapeutic Applications Of Polymersomesmentioning
confidence: 99%
“…A variety of HBOCs exist and include: recombinant Hbs [4], cross-linked Hbs [5], polymerized Hbs [6][7][8][9], PEGylated Hbs [10], liposome encapsulated Hbs [11][12][13], polymersome encapsulated Hbs [14] and other particle encapsulated Hbs [15][16][17]. In order to synthesize and/ or formulate these HBOCs, a pure source of Hb is needed.…”
Section: Introductionmentioning
confidence: 99%
“…A third group, particulate haemoglobin preparations able to carry other useful substances such as enzymes are also studied, but their development is still far from any clinical application [48][49][50][51].…”
Section: Haemoglobin Oxygen Carriers and Perioperative Organ Perfusimentioning
confidence: 99%
“…Unlike liposomes, polymersomes can be completely covered by polyethylene-glycol (PEG). PEG is a biologically inert polymer, used in drug delivery systems and known to be safe for in-vivo administration [48]. It influences the permeability of polymersomes, giving them better mechanical resistance with favourable osmotic properties, thus reducing problems with osmotic pressure gradients.…”
Section: Polymersome Encapsulated Haemoglobin (Peh)mentioning
confidence: 99%